Processing Development of Instant Juice Powder Product from Carrot Orange and Lemon by Using Foam Mat Drying - Wirivutthikorn, Wattana (Burapha Science Journal, 2026)
This research was a study of the production process of carrot, orange and lemon powder using foam-mat drying, which is done in order to produce drinking powder products. The purpose of this research was to study the optimum ratios of carrot, orange and lemon for producing instant powder using foam mat drying. Ratio of carrot, orange and lemon was performed into 6 treatments, which were Treatment 1 (control): 100:0:0, Treatment 2: 75:20:5, Treatment 3: 70:20:10, Treatment 4: 50:40:10, Treatment 5: 50:45:5 and Treatment 6: 62:31:7. The results showed that brightness, color (L*, a*, b*) and solubility of samples in all treatments were not significantly different (p>0.05). The chemical characteristics including pH, moisture, total soluble solid, vitamin C, b-carotene and antioxidant were investigated. The results indicated that ratio of carrot, orange and lemon (50:40:10) had the highest antioxidant and b-carotene values of 3.68 mg Trolox eq/g and 0.14 µg/100g FW, respectively. The sensory evaluation on taste and overall acceptability using 9-point hedonic scale revealed that panelists accepted on Treatment 4 which gave the highest scores of 5.70 and 6.33, respectively